Epidemiology, Management, and Survival of Peritoneal Carcinomatosis from Colorectal Cancer: A Population-Based Study. Issue 8 (August 2015) - Quere, P.; Facy, O.; Manfredi, S.; Jooste, V.; Faivre, J.; Lepage, C.; Bouvier, A.-M.
Abstract : BACKGROUND: Modern chemotherapy aims to improve long-term survival for selected patients with peritoneal carcinomatosis. Publications suggest promising results, but the spread of these new aggressive treatment strategies in the general population is not well known. OBJECTIVE: The aim of this study was to draw a picture of epidemiology, management, and survival in synchronous and metachronous peritoneal carcinomatosis from colorectal cancer. DESIGN: The cumulative risk of metachronous peritoneal carcinomatosis was estimated in patients resected for cure. Net survival rates were calculated for synchronous and metachronous peritoneal carcinomatosis. SETTINGS: The study was conducted with the use of the Burgundy Digestive Cancer Registry. PATIENTS: Overall, 9174 primary colorectal cancers registered between 1976 and 2011 by the population-based digestive cancer registry were considered. RESULTS: In total, 7% of patients were diagnosed with synchronous peritoneal carcinomatosis. The 5-year cumulative risk of metachronous peritoneal carcinomatosis was 6%, and the stage of the colorectal cancer at diagnosis was the major risk factor. Other independent risk factors were mucinous adenocarcinoma, ulceroinfiltrating tumors, and diagnosis after obstruction or perforation. The proportion of patients resected for cure was 11% and 9% for synchronous and metachronous peritoneal carcinomatosis, and 3-year overall net survival was 8% and 5%. The corresponding rates after resection for cure were 21% and 17%. There was a dramatic increase in the proportion of patients receiving systemic chemotherapy: from 11% before 1997 to 48% in 2011 for synchronous peritoneal carcinomatosis and from 3% to 38% for metachronous peritoneal carcinomatosis. LIMITATIONS: This is a retrospective observational population-based study. CONCLUSION: Peritoneal carcinomatosis complicating colorectal cancer is a major reason for treatment failure. This study identified patients at a high risk of developing peritoneal carcinomatosis who may benefit from specific surveillance. New therapeutic modalities are also needed to improve the prognosis.